Reduction in physical activity significantly increases depression and anxiety in the perinatal period: a longitudinal study based on a self-report digital assessment tool - Haßdenteufel, Kathrin; Feißt, Manuel; Brusniak, Katharina; Lingenfelder, Katrin; Matthies, Lina; Wallwiener, Markus; Wallwiener, Stephanie (Archives of gynecology and obstetrics, 2020)
Physical activity can reduce pregnancy-related complications and contributes substantially to improving maternal mental health. A reduction in activity encompassing exercise and daily household tasks throughout the course of pregnancy increases the risk of depression and anxiety. The following research examines the longitudinal interaction between exercise, general physical activity, and mental health outcomes in pregnant women.
Gesehen am 09.09.2021